2021
DOI: 10.18178/ijiet.2021.11.3.1501
|View full text |Cite
|
Sign up to set email alerts
|

The Shift to Online Education Paradigm due to COVID-19: A Study of Student’s Behavior in UAE Universities Environment

Abstract: The shift to an online education paradigm has been dramatically seen in educational systems and universities due to COVID-19 across the world, especially in United Arab Emirates. The emergence of COVID-19 forced educational institutions to divert all strategies from physical to online platforms for the safety of students, instructors and all the other staff members. However, this is not the case in educational institutions only because other governmental and non-governmental institutions are affected in the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 19 publications
5
17
2
Order By: Relevance
“…The results of the current research agree with several study results indicating students' satisfaction with online courses (Ali, 2021;Al-Kaf & Al-Balushi, 2021;Chanchalor & Powichai, 2003;Hazeri & Farzin-Yazdi, 2015;Kahawan, 2014;Manhray, 2015;Ong & Lai, 2006;Sharhan, 2003). However, these results, along with other results, indicate that students are not satisfied with the experience of ecourses in general and the distance field training in particular (Himat et al, 2021;Shehat & Al-Amri, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…The results of the current research agree with several study results indicating students' satisfaction with online courses (Ali, 2021;Al-Kaf & Al-Balushi, 2021;Chanchalor & Powichai, 2003;Hazeri & Farzin-Yazdi, 2015;Kahawan, 2014;Manhray, 2015;Ong & Lai, 2006;Sharhan, 2003). However, these results, along with other results, indicate that students are not satisfied with the experience of ecourses in general and the distance field training in particular (Himat et al, 2021;Shehat & Al-Amri, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…This study is essential because 2020 is the year when people were obliged to use e-learning technologies due to COVID-19; however, this study only explores the students' perspectives, and does not investigate the points of view of academics in higher education institutes. Furthermore, Ali [38] discussed the dramatic shift to online education in the UAE during the COVID-19 pandemic and indicated that e-learning has provided the education system with the flexibility that a traditional education system has not been able to provide. Additionally, the researcher argued that students were more focused on autonomous learning which minimized the load on the instructor.…”
Section: Higher Education In the Uae During Covid-19mentioning
confidence: 99%
“…To sum up, one thing is sure: face-to-face association can't be rejected from the instructive interaction. Students should be able to choose whether they would like to enroll in an online or physical course [33]. Campus needs to consider that, campus is not only a place for education, but it is also considered as a sanctuary for many students [34].…”
Section: Findings Of the Objective Threementioning
confidence: 99%